The reliability of the McCabe score as a marker of co-morbidity in healthcare-associated infection point prevalence studies. Issue 3 (May 2016) - Reilly, JS; Coignard, B; Price, L; Godwin, J; Cairns, S; Hopkins, S; Lyytikäinen, O; Hansen, S; Malcolm, W; Hughes, GJ
This study aimed to ascertain the reliability of the McCabe score in a healthcare-associated infection point prevalence survey. A 10 European Union Member States survey in 20 hospitals (n = 1912) indicated that there was a moderate level of agreement (κ = 0.57) with the score. The reliability of the application of the score could be increased by training data collectors, particularly with reference to the ultimately fatal criteria. This is important if the score is to be used to risk adjust data to drive infection prevention and control interventions.